0
$\begingroup$

Let $m,n$ be integers satisfying the condition $m\le 3(n+1)$.

Prove the identity $$\sum\limits_{k\ge 0} (-1)^k{n+1\choose k}{n+m-4k\choose n}=\sum\limits_{k\ge 0}{n+1\choose k}{n+1\choose m-2k}$$

$\endgroup$
1
$\begingroup$

I have just found the way solve this problem. $$$$ We have $$\left\langle x^m\right\rangle\left[(1+x+x^2+x^3)^{n+1}\right]=\left\langle x^m\right\rangle\left[(1+x)^{n+1}(1+x^2)^{n+1}\right]=\left\langle x^m\right\rangle\left[\left(\dfrac{1-x^4}{1-x}\right)^{n+1}\right]$$ $$\begin{eqnarray*}(1+x)^{n+1}(1+x^2)^{n+1}&=&\sum_{k=0}^{n+1}{n+1\choose k}x^k\sum_{j=0}^{n+1}{n+1\choose j}x^{2j}\\&=&\sum_{k=0}^{n+1}\sum_{j=0}^{n+1}{n+1\choose k}{n+1\choose j}x^{k+2j}\end{eqnarray*}$$ $$\tag{1}\Rightarrow \left\langle x^m\right\rangle\left[(1+x)^{n+1}(1+x^2)^{n+1}\right]=\sum_{j=0}^{n+1}{n+1\choose m-2j}{n+1\choose j}$$ Other way $$\begin{eqnarray*}\left(\dfrac{1-x^4}{1-x}\right)^{n+1}&=&\sum_{k=0}^{n+1}{n+1\choose k}(-1)^kx^{4k}\sum_{j\ge 0}{n+j\choose j}x^j\\&=&\sum_{j\ge 0}\sum_{k=0}^{n+1}{n+1\choose k}{n+j\choose j}(-1)^kx^{4k+j}\end{eqnarray*}$$ $$\tag{2}\Rightarrow \left\langle x^m\right\rangle\left[\left(\dfrac{1-x^4}{1-x}\right)^{n+1}\right]=\sum_{k\ge 0}{n+1\choose k}{n+m-4k\choose m-4k}(-1)^k$$ $(1)\quad\&\quad(2)\Rightarrow Q.E.D$


P/s: My english very bad :(

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.